Perlindungan Kepentingan Umum dalam Hukum Persaingan Usaha di Indonesia: Analisis Undang-Undang Nomor 5 Tahun 1999 tentang Larangan Praktik Monopoli dan Persaingan Usaha Tidak Sehat - Damar Fattan Rohim; Siti Zahara; Irmayani Sitorus (Medan Resource Center, 2026)
This study examines how public interests are protected under Indonesia’s competition law framework, with particular emphasis on Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition. The research addresses the extent to which the existing legal framework effectively safeguards public interests by analyzing the philosophical foundations of competition law, its underlying principles and objectives, the legal classification of unfair business practices, and the enforcement mechanism implemented by the Business Competition Supervisory Commission (Komisi Pengawas Persaingan Usaha—KPPU). Employing a normative juridical approach, the study analyzes primary legal materials, including statutory regulations, together with secondary legal sources comprising scholarly literature and relevant legal doctrines. The findings demonstrate that Indonesian competition law serves not only as an instrument for promoting fair competition and economic efficiency but also as a mechanism for protecting consumers and preserving the public interest against monopolistic practices and unfair market conduct. Nevertheless, enforcement remains constrained by institutional limitations, regulatory fragmentation, and inconsistencies in the application of sanctions. The study concludes that strengthening institutional coordination, harmonizing sectoral regulations, and enhancing the effectiveness of enforcement mechanisms are essential to ensuring greater legal certainty, equitable market competition, and sustainable protection of the public interest.